4
$\begingroup$

We have the profit function of the firm profit = $p^2 -2p -399$.

We take derivative of it we say that the output supply function is =$2p-2$

I understand that Profit = q*p - TC But why do we say the output supply function is equal to it's first derivative? We are not maximizing here. Simply finding the derivative.

$\endgroup$
1
  • $\begingroup$ Did you mean to state the profit function only in terms of the output price $p$? $\endgroup$ Mar 20, 2023 at 12:52

2 Answers 2

3
$\begingroup$

First, this only works in perfect competition so it is not a general result. Second, the reason why it works is that, first derivative wrt quantity is the condition for maximizing profit. Profit maximizing firm would want to supply quantity to a market such that its profit is maximized. So firm supply will be given by q that satisfies this foc for given price.

$\endgroup$
2
  • $\begingroup$ In this exercise, we found the FOC in regards to price. Does it make any difference? $\endgroup$ Mar 20, 2023 at 12:52
  • 1
    $\begingroup$ @alioshakaramazov no, in that case q will still by implied by optimum p $\endgroup$
    – 1muflon1
    Mar 20, 2023 at 12:59
1
$\begingroup$

Hotelling’s Lemma states that for the indirect profit function $\Pi^\star(p,w,r)$, we have that the firm’s output supply is given by:

$q^s = \frac{d \Pi^\star}{dp}$

Here is its proof:

The optimized profit function is given by

$\Pi^\star(p,w,r) = \Pi(p,L^\star(p),K^\star(p))$

$ = p \cdot q(L^\star(p), K^\star(p)) - w L^\star(p) - r K^\star(p)$

Recall the optimality conditions for profit maximization are given by

$\frac{\partial \Pi}{\partial L}|_{L = L^\star} = 0$,

$\frac{\partial \Pi}{\partial K}|_{K = K^\star} = 0$.

Taking the total derivative of the optimized profit $\Pi^\star$ with respect to $p$ at the optimal inputs,

$\frac{d\Pi^\star}{dp} = \frac{\partial \Pi}{\partial L}|_{L=L^\star(p)} \frac{\partial L}{\partial w} + \frac{\partial \Pi}{\partial K}|_{K=K^\star(p)} \frac{\partial K}{\partial w} + \frac{\partial \Pi}{\partial p} = 0 + 0 + \frac{\partial \Pi}{\partial p} = \frac{\partial \Pi}{\partial p}$

$= q(L^\star(p),K^\star(p)) = q^s(p)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.